Abatement of Azo Dye from Wastewater Using Bimetal-Chitosan. (20th November 2013) - Asgari, Ghorban; Ramavandi, Bahman; Farjadfard, Sima
Abstract : We introduce a new adsorbent, bimetallic chitosan particle (BCP) that is successfully synthesized and applied to remove the orange II dye from wastewater. The effects of pH, BCP quantity, and contact time are initially verified on the basis of the percentage of orange II removed from the wastewater. Experimental data reveal that the Cu/Mg bimetal and chitosan have a synergistic effect on the adsorption process of the adsorbate, where the dye adsorption by Cu/Mg bimetal, chitosan alone, and bimetal-chitosan is 10, 49, and 99.5%, respectively. The time required for the complete decolorization of orange II by 1 mg/L of BCP is 10 min. The Langmuir model is the best fit for the experimental data, which attains a maximum adsorption capacity of 384.6 mg/g. The consideration of the kinetic behavior indicates that the adsorption of orange II onto the BCP fits best with the pseudo-second-order and Elovich models. Further, the simulated azo dye wastewater can be effectively treated using a relatively low quantity of the adsorbent, 1 mg/L, within a short reaction time of 20 min. Overall, the use of BCP can be considered a promising method for eliminating the azo dye from wastewater effectively.